2018
DOI: 10.1038/s41388-018-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

Klotho suppresses colorectal cancer through modulation of the unfolded protein response

Abstract: Klotho is an anti-aging transmembrane protein, which can be shed and function as a hormone. Accumulating data indicate klotho as a tumor suppressor in a wide array of malignancies and indicate the subdomain KL1 as the active region of the protein. We aimed to study the role of klotho as a tumor suppressor in colorectal cancer. Bioinformatics analyses of TCGA datasets indicated reduced klotho mRNA levels in human colorectal cancer, along with negative regulation of klotho expression by hypermethylation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
0
30
0
2
Order By: Relevance
“…They reported that klotho downregulation significantly increases ER stress and activation of UPR signaling upon treatment with agents disrupting ER homeostasis by affecting ER Ca 2+ pump and N-linked glycosylation of proteins [12]. Ameliorating effect of klotho on ER stress and its role in modulation of the unfolded protein response was described also in some other studies [13][14][15]. Moreover, the role of klotho in LPS-mediated ER stress was studied in a different cell model.…”
Section: Discussionmentioning
confidence: 86%
“…They reported that klotho downregulation significantly increases ER stress and activation of UPR signaling upon treatment with agents disrupting ER homeostasis by affecting ER Ca 2+ pump and N-linked glycosylation of proteins [12]. Ameliorating effect of klotho on ER stress and its role in modulation of the unfolded protein response was described also in some other studies [13][14][15]. Moreover, the role of klotho in LPS-mediated ER stress was studied in a different cell model.…”
Section: Discussionmentioning
confidence: 86%
“…The studies described above have suggested that senescent stromal cells may help promote the malignant behavior of CRC cells. Klotho, a widely recognized anti‐aging protein, was previously proposed to act as a tumor suppressor in CRC (Arbel Rubinstein et al ., ; Pan et al ., ). Pretreatment of the senescent WI‐38 with Klotho partially reversed the enhanced proliferation and invasion seen after treating the CRC lines with senescent WI‐38 CM.…”
Section: Resultsmentioning
confidence: 99%
“…The analyses of publicly available DNA methylation datasets revealed a specific site in the first exon of KLOTHO, within a CpG island, that is hypermethylated in human colorectal cancer. Hypermethylation of the first exon, as well as promoter hypermethylation, negatively regulated Klotho expression in colorectal cancer [69]. This group demonstrated that overexpression using HA-tagged Klotho via transfection resulted in a reduction of surviving cancer colonies by at least 85% in colorectal HCT-116 and HT-29 cells.…”
Section: Colorectal Cancermentioning
confidence: 95%
“…The investigators tested the effects of Klotho in vivo on either chemically induced carcinogenic, or orthotopic mouse models in which MC38 colorectal cancer cells were injected into the colonic submucosa. Mice treated with soluble Klotho exhibited significantly reduced weight and volume of the orthotopic tumour [69]. Furthermore, Klotho has been shown to be down-regulated through promoter methylation in 83.3% of colon cancer cell lines and 85% of primary colorectal cancer tissues [45].…”
Section: Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation